EXPERIMENTAL STUDY: DETERMINATION OF CONCRETE REINFORCEMENT CONDITIONS - Khalid Abdel Naser Abdel Rahim (The Journal of Engineering and Exact Sciences)
This paper is about the determination of concrete reinforcement conditions. The concrete rein-forcement condition testing is a process by which different test are carried out such as cover depth, concrete resistivity, ½ - cell mapping and chloride content, to determine how each test shows the effects of corrosion in the reinforced concrete. Four different types of tests were conducted on two different reinforced concrete cu-bes to investigate the embedded bar conditions. The tests were cover depth, concrete resistivity, ½ cell map-ping and chloride content tests. The experimental testing was carried out in the concrete laboratory at the Uni-versity of Dundee.